KINETICS AND ROLE OF PANCREATIC STONE PROTEIN AND MIDREGIONAL PROADRENOMEDULLIN AS PREDICTORS OF SEPSIS AND BACTEREMIA IN CHILDREN WITH HAEMATOLOGICAL MALIGNANCIES. - Antari, Vasiliki; Skoura, Lemonia; Tragiannidis, Athanasios; Hatzipantelis, Emmanuel; Tsinopoulou, Vasiliki-Rengina; Papakonstantinou, Konstantina; Protonotariou, Efthimia; Galli-Tsinopoulou, Assimina (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: To investigate the kinetics and prognostic value of pancreatic stone protein (PSP) and mid-regional proadrenomedullin (MR-proADM) during episodes of febrile neutropenia (FN) in children with haematological malignancies. Material and methods: We evaluated prospectively a total of 70 FN episodes in 70 children with acute leukemias and lymphomas. Levels of CRP, PSP and MR-proADM were measured at the onset of the febrile episode (day 1), on day 3 and on day 7. The outcome and survival of children were evaluated during the study period until day 28. The performance of each marker in identifying sepsis or severe sepsis was assessed as area under a receiver operating characteristic (ROC) curve. For each biomarker, ROC curves were used to derive cut-offs for sensitivity and specificity in distinguishing sepsis from non-sepsis. Results: During the 2-year study period, 70 febrile neutropenia episodes in 70 children with haematological malignancies were enrolled. Of 70 episodes of febrile neutropenia, in 17 (24%) a bacterial/fungal infection was documented. Criteria for sepsis were fulfilled for 31 (44%) and 7 (10%) patients were admitted to PICU. The median values of all biomarkers were higher on day 1 and differed significantly between patients with and without sepsis. The specificity of PSP, MR-proADM, and CRP were 0.82, 0.70, and 0.57, respectively. The sensitivity of PSP, MR-proADM and CRP were 0.84, 0.74, and 0.88, respectively. Conclusions: Both PSP and MR-proADM are promising biomarkers for early diagnosis of sepsis during FN episodes in children with haematological malignancies. PSP has the higher sensitivity and specificity.